Role of Combined Pleural Fluid Cholesterol and Total Protein in Differentiation of Exudates and Transudates - Bista, Anupam; Thapa, Suman; Subedi, Prasant; Manandhar, Kiran (Nepalese Medical Journal, 2020)
Introduction: Light's criteria had been the standard method for distinguishing exudative and transudative pleural effusions which misidentify 15-20% of transudates as exudates. This study aims to find out the role of combined pleural fluid cholesterol and total protein in distinguishing exudative from transudative pleural effusions and its applicability in Nepalese populations. Materials and Methods: Patients with pleural effusions were enrolled for the study. The combined pleural fluid cholesterol and total protein were compared with Light’s criteria and also compared with the diagnosis on discharge to find out their usefulness in categorizing the pleural effusions. Results: A total of 81 patients enrolled in the study, 42 (51.9%) were male. Based on Light’s criteria, 88.8% pleural effusions were found to be exudates and 11.1% were found to be transudates. Within the criteria, Light’s criteria categorized more pleural fluids as exudates than the diagnosis on discharge. Based on pleural fluid cholesterol >60mg/dL and protein >3g/dL for the classification of exudative and transudative pleural fluid, 62.9% out of 81 samples felled under the exudates and 37.03% pleural effusions under transudates with the sensitivity 87.9% and specificity 100%. Conclusions: Though Light’s criteria remain the gold standard to differentiate transudates and exudates, combined pleural fluid cholesterol and total protein give nearly comparable results without the need for simultaneous blood investigations.